Switching function parameter variation analysis of a quasi-sliding mode controlled induction motor drive - Asha Elizebath Daniel; Shaija Palackappillil (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Sliding mode control is a nonlinear, robust control that is having better load disturbance rejection capability, less parameter sensitivity and fast dynamic response. Conventional sliding mode control introduces high chattering that can degrade the induction motor (IM) drive system responses. Hence, a quasi-sliding mode controller (Q-SMC) using a hyperbolic tangent function coupled with equivalent control is designed for robust speed control of vector-controlled IM drive in this work. This work focuses on the effect of variation of the switching function parameters of the Q-SMC on the performance of the drive. Extensive simulations are performed using MATLAB/Simulink software, and the switching function parameters are adjusted across a wide range and its impact on motor performance is studied qualitatively and quantitatively, with accompanying graphical results and various transient parameters. It is observed that a Q-SMC controller with a larger boundary layer width has less overshoot, less steady-state error, and a lower current THD. It is also observed that even though a high gain Q-SMC controller responds quickly, the percentage overshoot for high gain systems is likewise large. Hence, if the boundary layer width and switching gain parameters are optimized, a Q-SMC speed controller is a promising choice for a high-performance IM drive.